Distinct activation phenotype of a highly conserved novel HLA‐B57‐restricted epitope during dengue virus infection. Issue 1 (January 2014) - Townsley, Elizabeth; Woda, Marcia; Thomas, Stephen J.; Kalayanarooj, Siripen; Gibbons, Robert V.; Nisalak, Ananda; Srikiatkhachorn, Anon; Green, Sharone; Stephens, Henry A.F.; Rothman, Alan L.; Mathew, Anuja
Summary Variation in the sequence of T‐cell epitopes between dengue virus (DENV) serotypes is believed to alter memory T‐cell responses during second heterologous infections. We identified a highly conserved, novel, HLA‐B57‐restricted epitope on the DENV NS1 protein. We predicted higher frequencies of B57‐NS126–34‐specific CD8+ T cells in peripheral blood mononuclear cells from individuals undergoing secondary rather than primary DENV infection. However, high tetramer‐positive T‐cell frequencies during acute infection were seen in only one of nine subjects with secondary infection. B57‐NS126–34‐specific and other DENV epitope‐specific CD8+ T cells, as well as total CD8+ T cells, expressed an activated phenotype (CD69+ and/or CD38+) during acute infection. In contrast, expression of CD71 was largely limited to DENV epitope‐specific CD8+ T cells. In vitro stimulation of cell lines indicated that CD71 expression was differentially sensitive to stimulation by homologous and heterologous variant peptides. CD71 may represent a useful marker of antigen‐specific T‐cell activation.